1998
DOI: 10.1093/nar/26.2.554
|View full text |Cite
|
Sign up to set email alerts
|

End effects in DNA recognition by zinc finger arrays

Abstract: The paradigmatic DNA binding domain from the transcription factor Zif268 contains three zinc finger modules in tandem repeat. When bound to their cognate DNA site the fingers read out the sequence of one DNA strand by making a linear series of successive base contacts. It is shown that the base-specific protein-DNA contacts made from the ends of the Zif268 three-finger array contribute less to the stability of the intermolecular complex than do structurally equivalent contacts from more central regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…42,44,45,47,63,71 This lack of quantitative modularity is compounded by end effects, as distal hydrogen bonds have been proposed not to be as highly constrained or shielded from the solvent as the more central ones. 65 Support for this hypothesis can be gained from inspection of the results for EGR1-f3 from our molecular dynamics simulation, which shows the largest standard deviation for the Arg6-G1 interaction (Table 2). Given the sequence differences between Sp1-f1 and Sp1-f3, their distinctive affinities might be a reflection of diminished sequence specificity on the part of Sp1-f1 and of differential end effects.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…42,44,45,47,63,71 This lack of quantitative modularity is compounded by end effects, as distal hydrogen bonds have been proposed not to be as highly constrained or shielded from the solvent as the more central ones. 65 Support for this hypothesis can be gained from inspection of the results for EGR1-f3 from our molecular dynamics simulation, which shows the largest standard deviation for the Arg6-G1 interaction (Table 2). Given the sequence differences between Sp1-f1 and Sp1-f3, their distinctive affinities might be a reflection of diminished sequence specificity on the part of Sp1-f1 and of differential end effects.…”
mentioning
confidence: 79%
“…42 Although a mutant containing Ala in place of His at position 3 of this finger has been reported to have practically the same affinity as wild-type Sp1 for a canonical GC box, 59 the authors did not address the issue of specificity, so that a definite role for His3 in base recognition cannot be ruled out. Other experiments have shown that mutation to Ala of similarly highly conserved residues such as Arg6 in finger 3 of EGR1 65 or in finger 2 of ADR1 66 (which is involved in both cases in binding to a guanine base according to the structural studies) can result in only a moderate reduction in complex stability. It is therefore likely that in Sp1-f1 the contribution of this histidine to the energetics of DNA binding may be not so great as that of the corresponding residue in finger 3.…”
Section: Zinc Finger 1 Of Sp1mentioning
confidence: 98%
“…2A), although modules at fingers 1 and 3 display lower median scores than those at finger 2. This is likely to be due to fraying effects at the edges of the protein-DNA complex that reduce the specificity of the determinants at these positions (Choo, 1998). Comparison of PWM values across all individual modules revealed that those targeting purine-rich triplets were among the most robust, regardless of their finger position.…”
Section: Binding Specificity Of Modularly Assembled Zfpsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In the large class of proteins capable of binding DNA, zinc finger proteins have been preferred for the design of artificial transcription factors on the basis of structural plasticity and modularity. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] As a result of the work of several research groups, a code that relates the amino-acid sequence of a single zincfinger domain to its associated DNA nucleotide triplet target has been established. This 'code' is described as 'syllabic', depending not only on invariant amino acid/base pair correspondence, but also on structural characteristics of every single zinc finger module and the context in which it is found.…”
Section: Introductionmentioning
confidence: 99%
“…This 'code' is described as 'syllabic', depending not only on invariant amino acid/base pair correspondence, but also on structural characteristics of every single zinc finger module and the context in which it is found. [7][8][9][10][11][12][13][14][15][16][17][18] The application of this 'code' permits the design of zinc finger domains potentially able to target a desired sequence. 5,7,11 Using the available code, we engineered new zinc-finger based transcription factors capable of binding and activating transcription from the promoter of the dystrophin related gene, 'utrophin'.…”
Section: Introductionmentioning
confidence: 99%